IoT-Based Battery Monitoring System for Electric Vehicle - Helmy Abd Wahab, Mohd; Imanina Mohamad Anuar, Nur; Ambar, Radzi; Baharum, Aslina; Shanta, Shanoor; Suffian Sulaiman, Mohd; Sanim Mohd Fauzi, Shukor; Fahri Hanafi, Hafizul (International Journal of Engineering and Technology, 2018)
This paper describes the application of Internet-of-things (IoT) in monitoring the performance of electric vehicle battery. It is clear that an electric vehicle totally depends on the source of energy from a battery. However, the amount of energy supplied to the vehicle is decreasing gradually that leads to the performance degradation. This is a major concern for battery manufacture. In this work, the idea of monitoring the performance of the vehicle using IoT techniques is proposed, so that the monitoring can be done directly. The proposed IoT-based battery monitoring system is consists of two major parts i) monitoring device and ii) user interface. Based on experimental results, the system is capable to detect degraded battery performance and sends notification messages to the user for further action. Â